The snowman / the snowman and the snowdog - Bowie, David; Briggs, Raymond; Briggs, Raymond; Hamish Hamilton Ltd.; NCircle Entertainment (United States Hamish Hamilton, 2015)
"The snowman: One crisp, winter morning, a young boy wakes up to find a thick blanket of snow has covered the ground as far as the eye can see. Filled with excitement, the boy decides to build a snowman using a tangerine for his nose, coal for his buttons and eyes, and tops him off with a hat and scarf. Later that night, at the stroke of midnight, the snowman comes to life."--Publisher's description.
"The snowman and the dog: When a young boy and his mother move to a new house, the boy discovers a secret box hidden under the floorboards of his bedroom. In the box, he finds a hat, scarf, some lumps of coal and a shriveled tangerine -- it's a snowman-making kit. Later that day it starts to snow and the boy builds a snowman and with the little spare snow leftover, a snowdog. That night they come to life and take him on a wonderful adventure."--Publisher's description.
Title from disc label.
Based on the adaption of the book by Raymond Briggs.
Bonus features: the story of The Snowman ; alternate introduction from David Bowie ; behind the scenes documentary and interview with Raymond Briggs.
David Bowie, Raymond Briggs.
DVD.
English dialogue.
Keywords: Santa Claus -- (Fictitious character) -- Juvenile films; Snowmen -- Juvenile films; Magic -- Juvenile films; Dogs -- Juvenile films; Winter -- Juvenile films; Snow -- Juvenile films; Television programs -- United States; Animated television programs; Children's television programs; Christmas television programs; Juvenile works; Children's films